Civic heroes; enhancing civic awareness through game-based learning / Nuqman Haziq Zulfikar Zikri, Mohd Nabil Zulhemay and Nurul Hidayah Mat Zain - Zulfikar Zikri, Nuqman Haziq; Zulhemay, Mohd Nabil; Mat Zain, Nurul Hidayah (College of Computing, Informatics, and Mathematics, 2024)
This project seeks to address a critical societal need by focusing on the enhancement of civic awareness among young adults in Malaysia through an innovative approach— game-based learning. Recognizing the pivotal role of civic engagement in shaping the future of communities, the motivation stems from a desire to empower the younger generation with a profound understanding of their civic responsibilities and rights. The methodology employed involves harnessing the inherent appeal of video games to captivate and educate. By integrating a game enjoyment scale, the project aims to measure the level of engagement and satisfaction experienced by users throughout the gameplay. This not only ensures an enjoyable experience but also provides valuable insights into the effectiveness of the game as an educational tool. The game's design prioritizes interactive elements that encourage active participation, critical thinking, and decision-making, mirroring real-world civic scenarios. Through this immersive experience, players are expected to develop a nuanced understanding of civic issues, democratic processes, and the importance of their role in societal progress. This research contributes to the growing field of serious games for education, demonstrating the potential of game-based learning in cultivating informed and engaged citizens. The findings are expected to provide practical insights into the intersection of game enjoyment and civic education, offering a novel and effective strategy for promoting civic awareness among the youth in Malaysia. As the project unfolds, it aspires to not only measure the success of its approach through the game enjoyment scale but also to inspire a new wave of civic-minded individuals who are equipped with the knowledge and motivation to actively contribute to the betterment of their communities and society at large.